Virginia Woolf As a Process-Oriented Thinker - Livert, David (Lexington Books, 2023)
In A Psychology of Food, Cooks, and Cooking, David Livert employs current psychological research and theory to provide insights into the ubiquitous human behavior of cooking. Livert’s book provides a novel perspective, reviewing current research on cooks and cooking in both psychology and food studies. This book organizes and summarizes the large and diverse body of research and theory in psychology to better understand cooks and the behavior of cooking. This volume uniquely applies psychological research and theory to both domestic and commercial kitchens, taking advantage of Livert’s two decades of research and scholarship on the intersection of social psychology and food preparation. A Psychology of Food, Cooks, and Cooking illustrates the important insights that major psychological theories and concepts add to our understanding of cooks and cooking.